2014
DOI: 10.1371/journal.pone.0089074
|View full text |Cite
|
Sign up to set email alerts
|

Does ‘You Are What You Eat’ Apply to Mangrove Grapsid Crabs?

Abstract: In tropical mangroves, brachyuran crabs have been observed to consume high percentages of leaf litter production. However, questions concerning their ability to assimilate this low-quality food remain, as stable isotope analysis of C and N does not seem to support assimilation. Individuals of the common eastern Australian mangrove grapsid Parasesarma erythodactyla feeding on a mangrove leaf litter or mangrove+microphytobenthos diet developed a significantly higher hepatosomatic index than those with access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 80 publications
(90 reference statements)
7
47
0
4
Order By: Relevance
“…Secondly, laboratory feeding trials have shown that trophic fractionation can be highly specific to the pairing of food and consumers, and in some extreme cases can vary by more than 5‰ in Δ 13 C or Δ 15 N when different combinations of arthropod consumers and food sources are involved ( e.g., Oelbermann & Scheu , Bui & Lee , Carvalho et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, laboratory feeding trials have shown that trophic fractionation can be highly specific to the pairing of food and consumers, and in some extreme cases can vary by more than 5‰ in Δ 13 C or Δ 15 N when different combinations of arthropod consumers and food sources are involved ( e.g., Oelbermann & Scheu , Bui & Lee , Carvalho et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Although mangroves only cover between 138,000 and 152,000 km 2 [ Giri et al ., ; Spalding et al ., ], these forested wetlands are of great value for their contributions to environmental, societal, and economic functions around the globe. In addition to providing habitat for numerous fauna and supporting food webs (directly and indirectly) [ Bui and Lee , ; Kristensen et al ., ; Nagelkerken et al ., ], natural resources for human communities [ Walters et al ., ] along with stabilization and protection of shorelines from tsunamis and storm surge [ Alongi et al ., ; Costanza et al ., ], these wetlands make a substantial contribution to the global carbon budget [ Bouillon et al ., ; Breithaupt et al ., ; Dittmar et al ., ; Donato et al ., ; Duarte et al ., ; Jennerjahn and Ittekkot , ; Mcleod et al ., ]. When looking specifically at the soil component of the budget, the quantitative research can be broadly categorized according to whether the focus is the organic carbon (OC) standing stock [ Adame et al ., ; Donato et al ., , 2012; Kauffman et al ., ] or the rate of OC burial [ Breithaupt et al ., , and references therein; Chmura et al ., ; Mcleod et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, MDS was developed as a technique for measuring the distance among psychological stimuli, which are presented as points in geometric space. The method now has extensive applications in different fields, e.g., ecology Bui and Lee (2014). It utilizes similarities between pairs of stimuli to identify a psychological distance between those stimuli.…”
Section: Mds Methodsmentioning
confidence: 99%
“…Creative, cost effective and environmental friendly ways are therefore required to explore approaches to manipulating water pollution (Tsaur et al, 2002). Stabilization pond, constructed wetland and other ecological land treatment systems are the centralized sewage treatment options, and ecological engineering that are employed to reduce water pollution and developed as sustainable ecosystems that have both human and ecological values (Mitsch, 2012). They have been used in both developed and developing countries, due to the general good performance in maintenance, minimal fossil fuel consumption (Crites et al, 2014;Kivaisi, 2001) as useful options for climate change adaptation.…”
Section: Introductionmentioning
confidence: 99%